Polyherbal formulation conjugated to gold nanoparticles induced ferroptosis in drug-resistant breast cancer stem cells through ferritin degradation - Chittineedi, Prasanthi; Mohammed, Arifullah; Abdul Razab, Mohammad Khairul Azhar; Mat Nawi, Norazlina; Pandrangi, Santhi Latha (Frontiers in Pharmacology, 2023)
Aim: Due to their minimal side effects, the anti-cancer properties of the polyherbal formulation are being investigated. However, due to their low absorption potential, the administration of polyherbal formulations is restricted. Loading the polyherbal formulation into gold nanoparticles enhances the bioavailability of the polyherbal formulation (PHF) accompanied by reducing the concentration of doxorubicin (dox). Ferroptosis is one of the novel pathways that specifically target cancer stem cells due to high ferritin levels. Hence, in the present study, we conjugated polyherbal formulation with gold nanoparticles and studied its effect on inducing ferroptosis in drug-resistant breast cancer cell lines. Materials and methods: PHF and dox conjugated to gold nanoparticles were characterized using FTIR, UV-Vis spectrophotometer, DLS, particle size analyzer, and XRD. The drug entrapment and efficiency studies were performed to assess the biodegradable potential of the synthesized gold nanoparticles. Paclitaxel-resistant breast cancer stem cells were generated, and an MTT assay was performed to evaluate the cytotoxicity potential of AuNP-PHF and AuNP-dox. Scratch assay and clonogenic assay were performed to assess the migration and proliferation of the cells after treatment with chosen drug combinations. The ability of PHF and dox conjugated to gold nanoparticles to induce ferritinophagy was evaluated by RT-PCR. Finally, image analysis was performed to check apoptosis and cellular ROS using inverted fluorescent microscope. The ability to induce cell cycle arrest was assessed by cell cycle analysis using flow cytometer. Results and conclusion: PHF and dox conjugated to gold nanoparticles showed high stability and showed to induce ferritin degradation in drug resistant breast cancer stem cells through ferritin degradation. AuNP-PHF in combination with low dose of AuNP-Dox nanoconjugate could be used as an effective cancer therapeutic agent, by targeting the autophagy necroptosis axis.